1989
DOI: 10.1111/j.1365-2125.1989.tb05357.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of monoamine oxidase by moclobemide: effects on monoamine metabolism and secretion of anterior pituitary hormones and cortisol in healthy volunteers.

Abstract: 1. Single oral doses (100, 200 and 300 mg) of moclobemide, a reversible inhibitor of monoamine oxidase (MAO) with predominant effects on the A‐ type of the enzyme, were administered to eight young, healthy male volunteers in a double‐blind, random‐order, placebo‐controlled study. The investigation was thereafter continued in an open fashion by administering a single 10 mg dose of the MAO‐B inhibitor deprenyl to the same subjects. 2. Deamination of catecholamines was powerfully and dose‐dependently inhibited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…This may be the result of dietary non-compliance. However, the effect of moclobemide on the deamination of 5-HT is known to be moderate (Koulu et al, 1989) probably because the affinity of the drug to the binding sites of the MAO is less than that of serotonin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be the result of dietary non-compliance. However, the effect of moclobemide on the deamination of 5-HT is known to be moderate (Koulu et al, 1989) probably because the affinity of the drug to the binding sites of the MAO is less than that of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…Moclobemide is a new, reversible (Waldmeier, 1985) MAO-A selective (Koulu et al, 1989;Wiesel et al, 1985) MAOI with few adverse effects and clear antidepressant properties (Casacchia et al, 1984;Dajas et al, 1984;Larsen et al, 1984;Stabl et al, 1989). Moclobemide penetrates well the brain, maximal concentrations of moclobemide in CSF are reached 2 h after oral administration and high CSF/plasma ratio (0.5) can be obtained (Lauy et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The low plasma levels found for harmine in the present study could explain the absence of a clear-cut MAO inhibitor effect on the urinary excretion of monoamine metabolites. The acute administration of a MAO-A inhibitor induces a decrease in the levels of oxidized deaminated monoamine metabolites and an increase in the levels of COMT-dependent methylated compounds (Pletscher, 1966;Koulu et al, 1989). Whereas in the present study normetanephrine, a methylated breakdown product of norepinephrine, showed statistically significant increases after dosing with ayahuasca, the levels of the deaminated metabolites measured, i.e., VMA, HVA, and 5-HIAA, did not show decreases but, rather, were nonsignificantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies have shown that when MAO is pharmacologically inhibited, the levels of MAO-dependent deaminated metabolites decrease and those of COMT-dependent methylated metabolites increase. In humans, MAO inhibitors decrease, after acute administration, the urinary excretion of vanillylmandelic acid (VMA), homovanillic acid (HVA), and 5-hydroxyindoleacetic acid (5-HIAA), the deaminated metabolites of norepinephrine/epinephrine, dopamine, and serotonin, respectively, while increasing that of metanephrine and normetanephrine, the methylated metabolites of epinephrine and norepinephrine, respectively (Pletscher, 1966;Koulu et al, 1989). Monoamine metabolites have both a CNS and a non-CNS origin, and their assessment in urine does not give information regarding the organ in which MAO was inhibited.…”
mentioning
confidence: 99%
“…The brain homogenate was stored at ª80ae until use. The MAO-A activity was determined according to Borbe et al (1990) and the MAO-B activity was determined according to Koulu et al (1989). The results were calculated as picomoles deaminated metabolite (5-hydroxyindole acetic acid or phenyl acetic acid) formed per min.…”
Section: Mao-a and Mao-b Activitymentioning
confidence: 99%